IMPLEMENTASI PROGRAM EKSTRAKURIKULER “BINA IMAN” DALAM PRESPEKTIF TOLERANSI SISWA MUSLIM DAN KATOLIK DI SMAS KATOLIK YOS SUDARSO KEPANJEN - Anggi Erika Dewi; Dwi Fitri Wiyono; Bagus Cahyanto (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
This research is a qualitative research with the type of case study research with the place of research at Yos Sudarso Catholic High School Malang. Data was collected using the methods of observation, interviews, and documentation. Data analysis is done by summarizing important data and then drawing conclusions. The program model of the